Preparation method of hydrophobic TPU (thermoplastic polyurethane) with high refractive index
By introducing zinc sulfide nanoparticles and fluoride modifiers into the TPU film, combined with polymerization reaction and chemical crosslinking technology, the problems of process complexity and environmental impact in the existing TPU preparation methods are solved, and the high refractive index and hydrophobicity are significantly improved.
Patent Information
- Application Number
- CN202411950845.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high-refractive index hydrophobic TPU preparation methods have problems such as process complexity, long reaction time, large environmental impact and poor uniformity of nanoparticles, which limit their feasibility and stability in large-scale production and long-term applications.
Bisphenol A and 4,4'-diphenylmethane diisocyanate were used as raw materials to synthesize polymer precursors through polymerization, and zinc sulfide nanoparticles and fluoride modifiers were introduced under nitrogen protection for chemical cross-linking and molding. Finally, the uniformity and adhesion of the coating were ensured by frozen aging and X-ray photoelectron spectroscopy (XPS) analysis.
The refractive index and hydrophobicity of the TPU film are improved, and the optical performance and waterproof performance of the material are significantly improved. At the same time, the process flow is simplified, the reaction time is shortened, and the environmental impact is reduced.
Smart Images

Figure CN119613649A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing TPU, in particular to a method for preparing high-refractive-index hydrophobic TPU. Background Art
[0002] Although the current preparation method for high-refractive index hydrophobic TPU has certain innovation and application value in the specific implementation process, it still has some shortcomings and disadvantages compared with other existing high-hardness transparent TPU preparation methods, especially in the overall improvement of material properties, optimization of preparation process and control of environmental impact. These problems limit the feasibility and stability of this method in large-scale production and long-term application to a certain extent. In combination with the preparation method of high-hardness transparent TPU proposed in the Chinese invention patent, patent number: 2021112344715, the following will elaborate on the shortcomings and disadvantages of the current preparation method of high-refractive index hydrophobic TPU.
[0003] First, the raw material preparation and reaction steps of the existing method are complicated and have certain process limitations. In the preparation process of this patent, a high-precision ratio of multiple raw materials is involved, including TCD (tetrachlorodiphenylmethane), short-chain diols, isocyanates and antioxidants, and each raw material needs to strictly control its addition order and proportion to ensure that a transparent and high-hardness TPU is finally obtained. This complex raw material matching and control method not only increases the difficulty of operation, but also puts forward high requirements on the technical level of production equipment and experimental personnel, resulting in poor stability and repeatability of the method in actual production. In the preparation process of high-refractive index hydrophobic TPU, although high-refractive index zinc sulfide nanoparticles and fluoride modification are used, the entire reaction system still faces similar cumbersome operations and process control difficulties. For example, the introduction of nanoparticles, the addition of surface modifiers, and precise control during chemical cross-linking all require precise equipment and strict experimental conditions, and these factors often affect the uniformity of the final product and the consistency of performance.
[0004] Secondly, in the existing TPU preparation method, some steps have too long reaction time, which seriously affects the production efficiency. In this patent, some reaction steps last for a long time, especially in the process of baking the material in step 3, the temperature requirement is 90-110°C, and the time needs to last for more than 70 hours. This process is not only time-consuming, but also high-temperature baking leads to the degradation of certain heat-sensitive materials, especially for the introduction and uniform dispersion of high-refractive index nanoparticles. Third, the traditional TPU preparation method involves the use of a large number of organic solvents and chemical additives, which to a certain extent brings potential risks to the environment and the health of production personnel. In this patent, some solvents such as dimethylformamide and various chemical additives such as antioxidants and anti-yellowing agents are required in the reaction. Although these chemicals can improve the performance of the final material, their use and treatment process impose a certain burden on the environment. For the preparation of high-refractive index hydrophobic TPU, although more environmentally friendly materials and processes are used, such as anhydrous ethanol as a dispersion medium, some organic solvents used in the dispersion and chemical modification of nanoparticles still have a certain impact on the environment and production operators.
[0005] In general, although the existing high-refractive-index hydrophobic TPU preparation method has certain advantages in terms of refractive index, hydrophobicity and chemical modification, it still has many shortcomings in terms of process complexity, reaction time, environmental friendliness, uniformity of nanoparticles and durability. In order to further enhance the practical application value and market competitiveness of this method, it is necessary to optimize the process flow, simplify the operation steps, shorten the reaction time, and explore more environmentally friendly and efficient materials and processes in the future to meet the needs of modern industry for high-performance, environmentally friendly and low-cost high-refractive-index hydrophobic TPU materials. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a high-refractive-index hydrophobic TPU, thereby solving some of the drawbacks and deficiencies pointed out in the background technology.
[0007] The present invention solves the above-mentioned technical problems by adopting the following technical solutions:
[0008] The following steps are involved:
[0009] S1. Synthesis of polymer precursor:
[0010] S1.1, Raw material preparation:
[0011] Bisphenol A and 4,4'-diphenylmethane diisocyanate are selected as raw materials, and the mass ratio is controlled between 1 part of bisphenol A and 2-3 parts of 4,4'-diphenylmethane diisocyanate; a mixture of bisphenol A and 4,4'-diphenylmethane diisocyanate is added into a four-necked flask reactor, anhydrous dimethylformamide is selected as the solvent, and the ratio of the solvent to the total raw materials is controlled between 2-3 parts;
[0012] S1.2, Polymerization reaction:
[0013] Under nitrogen protection, slowly raise the temperature to 80-90 degrees Celsius, maintain the stirring speed at 400-600 rpm, and react for 1-2 hours to allow bisphenol A and 4,4'-diphenylmethane diisocyanate to undergo a preliminary polymerization reaction;
[0014] The temperature is continued to rise to 110-130 degrees Celsius and maintained for 2-3 hours to allow the reaction to proceed completely to obtain the intermediate product prepolymer;
[0015] S1.3, cooling and termination of reaction:
[0016] The reaction temperature is gradually reduced to 60-80 degrees Celsius, and then 0.2-0.8 weight percent of a terminator including p-toluenesulfonic acid is added, and the reaction time is 20-40 minutes to stabilize the molecular structure of the prepolymer;
[0017] After the reaction is completed, the reaction system is slowly cooled to room temperature of 25 degrees Celsius to obtain a high-viscosity prepolymer liquid;
[0018] S2. Introduction of high refractive index components:
[0019] S2.1. Nanoparticle dispersion:
[0020] In the prepolymer solution cooled to 40-50 degrees Celsius, 15-25 weight percent of zinc sulfide nanoparticles are added dropwise, and the particle diameter is controlled in the range of 15-20 nanometers;
[0021] The zinc sulfide nanoparticles are treated in an ultrasonic disperser for 20 to 30 minutes in advance, and anhydrous ethanol is used as a dispersion medium, and the volume of the dispersion medium is 2 to 3 times the weight of the zinc sulfide;
[0022] S2.2. Preparation of nanocomposites:
[0023] Transfer the prepolymer solution containing zinc sulfide to a reaction kettle, raise the temperature to 50-70 degrees Celsius, and maintain it for 20-30 minutes to evenly distribute the zinc sulfide particles in the polymer matrix;
[0024] S3. Hydrophobic modification:
[0025] S3.1. Fluoride introduction:
[0026] In a clean reactor, 3 to 6 weight percent of potassium perfluorooctyl phosphate and 1 to 3 weight percent of bisphenol S are added as hydrophobic modifiers; the modifiers are added to the prepolymer-zinc sulfide solution, and slowly stirred at 50 to 70 degrees Celsius for 1 to 2 hours to allow the modifier to fully react with the polymer matrix;
[0027] S3.2, Chemical cross-linking:
[0028] 0.5-1.5 weight percent of triethylamine is added to the solution as a catalyst to accelerate the chemical cross-linking reaction of the hydrophobic group; the cooled material is poured into a mold for preliminary molding, and the mold is preheated to 50-70 degrees Celsius to obtain a preformed material.
[0029] Furthermore, the preformed material is placed in a laminator and pressurized at 70 to 90 degrees Celsius, with the pressure maintained at 40 to 60 MPa for 15 to 25 minutes to form a film with a thickness of 0.4 to 0.6 mm; after molding, the film is taken out of the mold and cooled to room temperature at room temperature to obtain a molded film.
[0030] Furthermore, the formed film is placed in a vacuum oven, the temperature is set to -15 to -5 degrees Celsius, and a freeze-aging treatment is performed for 48 to 72 hours; a hydrophobic coating is sprayed on the surface of the aged film, the coating uses a fluorine-containing polymer solution, and the coating thickness is controlled between 3 and 7 microns; after the coating is cured, the surface element distribution is confirmed by X-ray photoelectron spectroscopy XPS to ensure the uniformity and adhesion of the coating.
[0031] Furthermore, in step S2.1, the dispersed zinc sulfide solution is added dropwise to the prepolymer, and a high-speed shearing agitator is used to stir at 2500 to 3500 revolutions per minute for 1 to 1.5 hours.
[0032] Furthermore, in step S2.2, the temperature is increased to 110-130 degrees Celsius, the pressure is reduced to 400-600 mmHg, and stirring is continued for 1-1.5 hours.
[0033] Furthermore, in step S3.2, the reaction temperature is raised to 90-110 degrees Celsius and maintained for 2-3 hours; after the reaction is completed, the material is cooled to room temperature and stirred at a constant speed during the cooling process.
[0034] Furthermore, the X-ray photoelectron spectroscopy XPS technique is used to analyze the concentration distribution of each element in the coating, including tracking the distribution state of the high refractive index component zinc sulfide nanoparticles; and to describe the distribution of elements on the coating surface and at different depths, an element concentration distribution function C(x) is constructed, where x represents the position of the measurement point, and C(x) represents the element concentration at position x; and through integral analysis, the spatial distribution of elements on the coating surface is provided;
[0035]
[0036] Where C(x) is the element concentration at position x, indicating the element content at different positions on the coating surface; x 0 With x 1 is the integration interval, which indicates the analysis position interval selected during the XPS analysis process; I(λ) is the intensity of X-ray photoelectrons, which represents the relative concentration of each element in the coating; A(λ) is the absorption coefficient, which indicates the absorption characteristics of the coating by X-rays of different wavelengths, reflecting the reaction intensity of different elements at a specific wavelength.
[0037] Furthermore, the X-ray photoelectron spectroscopy XPS technique is used to analyze the chemical bonding strength between the coating and the atomic layer on the surface of the substrate; by XPS analysis at different depths, the interface element information between the substrate and the coating is obtained, and the adhesion function S(α) is constructed to describe the chemical bonding force between the coating surface and the substrate;
[0038]
[0039] Among them, S(α) is the chemical bonding strength, which indicates the bonding force between the coating and the substrate, reflecting the chemical bonding strength between the coating and the substrate; P(E) is the energy distribution of photoelectrons in the XPS signal, indicating the proportion of photoelectrons with different energies in the analysis process; E α is the characteristic energy associated with chemical bonds, reflecting the breaking of different chemical bonds; It is a function that represents energy decay, reflecting the law that chemical bonding strength decays with energy, where α is the type parameter of the chemical bond and E is the energy of the electron.
[0040] Furthermore, the X-ray photoelectron spectroscopy XPS technique is used to reveal the presence of uneven areas or defects on the coating surface through in-depth analysis of surface elements; a coating uniformity function U(x) is defined, and the function quantifies the difference in element concentration at each position of the coating, thereby evaluating the uniformity of the coating;
[0041]
[0042] Among them, U(x) is the uniformity function, which quantifies the difference in the concentration of coating elements and reflects the uniformity of the coating in space; N is the total number of measurement points, which represents the number of different locations selected on the coating surface; C(x i ) is the element concentration at the i-th measurement point, indicating the element content at the i-th position on the coating surface; C avg is the average concentration of the coating, which means the average value of the element concentration of all measuring points of the coating.
[0043] The beneficial effects of the preparation method of the high refractive index hydrophobic TPU of the present invention are mainly reflected in the following aspects:
[0044] 1. By introducing high-refractive-index zinc sulfide (ZnS) nanoparticles into a polyurethane (TPU) matrix, the present invention effectively increases the refractive index of the film. Compared with conventional TPU materials, the refractive index of the film prepared by this method can reach between 1.5 and 1.7. This enables the material to have better optical properties in optical applications such as optical coatings, display protective films, optical fibers, and the like.
[0045] 2. By modifying the TPU film with fluoride, the film is given excellent hydrophobic properties. After the introduction of fluoride modifiers (such as potassium perfluorooctyl phosphate), the contact angle of the film is significantly increased, and the contact angle can reach more than 120°, indicating that the film surface has good water drop repellency. The hydrophobicity makes the material self-cleaning, avoids the adhesion of surface pollutants, effectively extends the service life of the film, and reduces maintenance costs.
[0046] 3. XPS analysis technology was used to successfully reveal the uniformity and adhesion of the coating through in-depth analysis of the interface elements between the coating and the substrate. By introducing chemical cross-linking agents and hydrophobic modifiers, the chemical bonding strength between the coating and the substrate can be effectively improved, ensuring that the coating does not fall off or peel off during long-term use, thereby increasing the mechanical strength and durability of the film. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 The present invention defines a flow chart of each function by using X-ray photoelectron spectroscopy XPS technology. DETAILED DESCRIPTION
[0048] The specific implementation modes of the present invention will be described in detail below in conjunction with the accompanying drawings.
[0049] Embodiment 1:
[0050] This embodiment aims to prepare a high refractive index hydrophobic TPU (thermoplastic polyurethane) film; the specific preparation process includes the synthesis of polymer precursors, the introduction of high refractive index components and surface hydrophobicity modification. By introducing nano zinc sulfide particles and fluoride modification, a TPU film with high refractive index and excellent hydrophobicity is prepared.
[0051] Raw materials and equipment selection:
[0052] 1. Raw material selection:
[0053] Bisphenol A: A starting monomer used to synthesize polyurethane. Bisphenol A molecular weight: 228.3 g / mol.
[0054] 4,4'-Diphenylmethane diisocyanate (MDI): A high molecular weight isocyanate monomer used to react with bisphenol A, molecular weight: 250.3 g / mol.
[0055] Anhydrous dimethylformamide (DMF): as solvent, molecular weight: 73.1 g / mol.
[0056] Zinc sulfide (ZnS) nanoparticles: nanoparticles with a higher refractive index, with a diameter controlled at 15 to 20 nanometers, used to increase the refractive index of the final TPU material.
[0057] Potassium perfluorooctyl phosphate (PFOPA): used for hydrophobic modification, molecular weight: 400.5 g / mol.
[0058] Bisphenol S (BPS): used in combination with potassium perfluorooctyl phosphate to promote enhanced hydrophobicity, molecular weight: 252.3 g / mol.
[0059] Triethylamine (TEA): used as a cross-linking catalyst to promote chemical cross-linking reactions, molecular weight: 101.2 g / mol.
[0060] 2. Equipment selection:
[0061] Four-necked flask reactor: used for polymerization and stirring of reactants, equipped with temperature and stirring speed control system.
[0062] Ultrasonic disperser: used to disperse zinc sulfide particles to ensure uniform distribution of nanoparticles.
[0063] Reactor: used for mixing and temperature control after the introduction of nanoparticles.
[0064] Laminator: used for forming thin films, with temperature and pressure control functions.
[0065] Vacuum oven: used for freeze aging treatment.
[0066] X-ray Photoelectron Spectrometer (XPS): used for surface analysis to detect coating uniformity and adhesion.
[0067] Detailed description of the preparation process
[0068] 1. Synthesis of polymer precursor (S1)
[0069] 1.1 Raw material preparation:
[0070] Raw material ratio: the mass ratio of bisphenol A to 4,4'-diphenylmethane diisocyanate is 1:2.5.
[0071] Assuming that 500g TPU film needs to be prepared, then:
[0072]
[0073] Mass of 4,4'-diphenylmethane diisocyanate = 500 - 142.857 = 357.143 g
[0074] Solvent preparation: Anhydrous dimethylformamide (DMF) was selected as the solvent, and the mass ratio of the solvent to the total raw materials was 2.5.
[0075] Solvent mass = (142.857 + 357.143) × 2.5 = 1250 g
[0076] 1.2 Polymerization reaction:
[0077] Reaction conditions:
[0078] Bisphenol A, MDI and solvent (DMF) were added into the reactor.
[0079] Under nitrogen protection, slowly heat to 80-90°C and maintain the stirring speed at 500 rpm.
[0080] The reaction time is 1 hour, so that bisphenol A and MDI are initially polymerized to form a prepolymer.
[0081] Reaction equation (by thermal polymerization):
[0082] Bisphenol A+MDI→polymer prepolymer
[0083] The temperature is continued to rise to 110-130°C and the reaction is carried out for 2-3 hours to complete the polymerization reaction and obtain a prepolymer.
[0084] 1.3 Reaction termination and cooling:
[0085] After the reaction is completed, the temperature of the reactor is lowered to 60-80° C., and 0.5% p-toluenesulfonic acid terminator is added to terminate the reaction.
[0086] Terminator mass = 500 × 0.005 = 2.5 g
[0087] After cooling to room temperature, a high-viscosity polymer prepolymer is obtained.
[0088] 2. Introduction of high refractive index components (S2)
[0089] 2.1 Dispersion of Nano-ZnS Particles
[0090] Quality of nanoparticles: Use 15-25% zinc sulfide nanoparticles, set to use 20% addition:
[0091] Mass of zinc sulfide = 500 × 0.2 = 100 g
[0092] Dispersion solvent: Use anhydrous ethanol, the volume of the solvent is 2.5 times the weight of the zinc sulfide particles:
[0093] Ethanol solvent volume = 100 × 2.5 = 250 mL
[0094] Ultrasonic dispersion: Use an ultrasonic disperser to disperse the zinc sulfide particles for 20 to 30 minutes to ensure that the particles are evenly distributed.
[0095] 2.2 Preparation of Nanocomposites:
[0096] The dispersed zinc sulfide solution is mixed with the polymer prepolymer solution.
[0097] Heating reaction: Transfer to a reactor, raise the temperature to 60°C, and continue stirring for 30 minutes to ensure that the zinc sulfide particles are evenly dispersed in the polymer matrix.
[0098] 3. Hydrophobic modification (S3):
[0099] 3.1 Fluoride introduction
[0100] Modifier ratio: potassium perfluorooctyl phosphate (PFOPA) and bisphenol S are added in a mass ratio of 4:1.
[0101] Add fluoride modifier at 5% of the prepolymer mass:
[0102] Total mass of modifier = 500 × 0.05 = 25 g
[0103]
[0104] Reaction conditions: Add the modifier to the prepolymer-zinc sulfide solution and stir at 50-70°C for 1-2 hours to promote the hydrophobic reaction.
[0105] 3.2 Chemical cross-linking:
[0106] Catalyst addition: 0.8% triethylamine (TEA) was added as a catalyst to promote the cross-linking reaction of the hydrophobic groups.
[0107] Cross-linking reaction: Pour the cooled material into the mold, preheat it to 60°C, and perform preliminary molding.
[0108] 4. Molding and post-processing (S4)
[0109] 4.1 Film forming
[0110] The preformed material was transferred to a laminator, the temperature was set at 70-90°C, a pressure of 40-60 MPa was applied for 15-25 minutes, and a film with a thickness of 0.5 mm was formed.
[0111] 4.2 Freeze aging treatment
[0112] The formed film is placed in a vacuum oven and subjected to a freeze aging treatment at a temperature between -15°C and -5°C for 48 to 72 hours to ensure the stability of the polymer molecular chain.
[0113] 4.3 Surface hydrophobic coating
[0114] Coating material: Use fluorinated polymer solution for surface spraying, and the coating thickness is controlled at 5 microns.
[0115] Coating curing: After the coating is cured, X-ray photoelectron spectroscopy (XPS)
[0116] Analysis confirms coating uniformity and adhesion.
[0117] 4. Performance test of final product
[0118] In the process of preparing high refractive index hydrophobic TPU film, product performance testing is a key step to ensure that the final film meets the expected application requirements. The following is a detailed description and data results of the refractive index test, hydrophobicity test and XPS analysis.
[0119] 4.1 Refractive index test
[0120] The refractive index is an important indicator for evaluating the optical properties of a material. In this embodiment, due to the introduction of high refractive index zinc sulfide (ZnS) nanoparticles, it is expected that the refractive index of the final film can reach 1.5 to 1.7.
[0121] In order to accurately test the refractive index, an Abbe refractometer was used, which is a high-precision device capable of measuring the refractive index of materials in the visible light band (approximately 400nm to 700nm).
[0122] Test method:
[0123] 1. Use Abbe refractometer to test the sample.
[0124] 2. Measurement wavelength: 589nm (sodium light) and 546nm (green light).
[0125] 3. Sample preparation: Take out the TPU film that has been molded and freeze-aged, with a thickness of 0.5 mm.
[0126] Test steps:
[0127] 1. Place the film sample in the test station of the Abbe refractometer.
[0128] 2. Read the refractive index value of the sample by adjusting the instrument.
[0129] 3. Repeat the measurement three times and obtain the average value.
[0130] Expected results: Based on the refractive index of zinc sulfide (about 2.4), it is expected that the refractive index of TPU film can be increased to 1.5-1.7 through the introduction of nanoparticles.
[0131] Implementation results (test data):
[0132] sample Measurement wavelength (nm) Refractive index n TPU film without added particles 589 1.48 TPU film (with zinc sulfide particles added) 589 1.62 TPU film (with zinc sulfide particles added) 546 1.64
[0133] Data analysis: By introducing zinc sulfide nanoparticles, the refractive index of the film is indeed significantly improved, from 1.48 to 1.62-1.64, verifying the effectiveness of zinc sulfide in improving the refractive index.
[0134] 4.2 Hydrophobicity test:
[0135] Hydrophobicity is a key parameter to measure the waterproofness, weather resistance and other properties of a material. This embodiment adopts the contact angle measurement method (Contact Angle Measurement) to quantitatively evaluate its hydrophobicity by testing the contact angle of a water droplet on the surface of the film. A contact angle greater than 120° generally indicates that the material has good hydrophobicity.
[0136] Test method:
[0137] 1. Use an optical contact angle meter to test.
[0138] 2. Sample: TPU film after freeze aging and fluoride coating treatment, thickness 0.5mm.
[0139] 3. Test liquid: distilled water, drop volume is 2μL.
[0140] Test steps:
[0141] 1. Place the film sample on the test platform of the contact angle meter.
[0142] 2. Use a syringe to accurately add distilled water (2 μL) onto the film surface.
[0143] 3. Use a contact angle meter to automatically record the contact angle of the water droplet, repeat the measurement three times, and obtain the average value.
[0144] Expected results: Due to the introduction of the fluoride coating, the surface should exhibit high hydrophobicity and the contact angle is expected to be greater than 120°.
[0145] Implementation results (test data):
[0146] sample Water drop contact angle (°) Remark TPU film (unmodified) 95° More hydrophilic surface TPU film (with zinc sulfide added) 110° The surface has a certain degree of hydrophobicity TPU film (fluoride modified) 128° High hydrophobicity TPU film (fluoride modified + zinc sulfide) 133° Very high hydrophobicity
[0147] Data analysis: The hydrophobicity of the film was significantly improved by fluoride modification and the introduction of zinc sulfide particles. Finally, the contact angle reached 133°, which is much higher than that of general hydrophilic materials, showing extremely high hydrophobicity, proving that the synergistic effect of fluoride coating and nanoparticles significantly improved the hydrophobicity of the material.
[0148] 4.3 XPS analysis
[0149] X-ray photoelectron spectroscopy (XPS) is an important means of analyzing the distribution of elements, chemical state and adhesion on the surface of a film. In this embodiment, XPS is used to verify the uniformity and adhesion of the fluoride coating. XPS analysis can determine the presence of fluorine and whether the coating is evenly distributed on the surface of the TPU film.
[0150] Test method:
[0151] 1. Use an XPS instrument (such as ThermoFisher ESCALAB 250Xi) to analyze the sample.
[0152] 2. Test range: 1000eV (incident photoelectron beam energy), scanning angle is 45°.
[0153] 3. Sample: TPU film treated with fluoride coating.
[0154] Test steps:
[0155] 1. Place the TPU film sample on the sample stage of the XPS instrument.
[0156] 2. Irradiate the sample surface with an X-ray beam to obtain the XPS spectrum of the sample.
[0157] 3. Analyze the element peaks in the spectrum, especially the intensity ratio of fluorine (F1s) and carbon (C1s).
[0158] Expected results:
[0159] 1. Fluorine element (F1s) should appear as a strong peak in the spectrum, indicating the successful introduction of the fluoride coating.
[0160] 2. The change in the carbon element (C1s) peak should indicate the bonding of the fluoride coating to the polymer matrix.
[0161] Implementation results (test data):
[0162] element Binding Energy eV Intensity (relative intensity) Remark C1s 284.8 100% Carbon-based polymer matrix F1s 688.5 30% Fluoride coating O1s 531.3 20% Surface oxide layer N1s 399.2 10% Derived from residual nitrogen groups in polymers
[0163] Data analysis: XPS spectra show that the fluorine element (F1s) peak is obvious, indicating that the fluoride coating is successfully attached to the surface of the TPU film. The relative intensity of the fluoride coating is 30%, showing that the coating is evenly distributed on the surface. At the same time, the intensity of the C1s peak remains basically unchanged, indicating that the polymer matrix has not changed significantly. Combining these data, it can be inferred that the fluoride coating has strong adhesion and evenly covers the surface of the film.
[0164] 5. Final performance summary:
[0165] Refractive index: By introducing zinc sulfide nanoparticles, the refractive index of the TPU film increased from 1.48 to 1.62-1.64, indicating that the film has excellent optical properties.
[0166] Hydrophobicity: Through the synergistic effect of fluoride modification and zinc sulfide particles, the contact angle of the TPU film reaches 133°, showing extremely strong hydrophobicity.
[0167] XPS analysis: The fluoride coating is evenly attached to the film surface, ensuring the long-term hydrophobicity and stability of the film.
[0168] Product comparison:
[0169]
[0170] These test results show that this product has significant advantages over ordinary TPU on the market in terms of refractive index and hydrophobicity, and has broader application prospects, such as in optics, electronics, and waterproof coatings.
[0171] Example 2: Preparation of high refractive index hydrophobic TPU
[0172] 1. Raw material preparation:
[0173] 1. Raw material selection and preparation: Bisphenol A: As a polymer precursor, the mass is 100g.
[0174] 4,4'-diphenylmethane diisocyanate (MDI): 250g, used to react with bisphenol A to form a polyurethane skeleton. The mass ratio of the two is 1:2.5.
[0175] Anhydrous dimethylformamide (DMF): As a solvent, the amount added is 250g, so that the reaction system has good fluidity and solubility. The mass ratio of solvent to raw material is 1:1.
[0176] Ingredients and proportions:
[0177] Bisphenol A: 100g
[0178] MDI: 250g
[0179] Anhydrous DMF: 250g
[0180] 2. Mixed operation:
[0181] 100 g of bisphenol A and 250 g of 4,4'-diphenylmethane diisocyanate (MDI) were accurately weighed and added to a four-necked flask reactor. 250 g of anhydrous DMF was added as a solvent to ensure that all solid raw materials were completely dissolved to obtain a uniform solution.
[0182] 2. Polymerization reaction:
[0183] S1.2 Polymerization reaction:
[0184] Preliminary polymerization: Under nitrogen protection, the solution in the reactor is slowly heated to 90°C, the stirring speed is maintained at 500 rpm, and the reaction is maintained for 1.5 hours. At this time, MDI reacts with bisphenol A to generate a preliminary polymer.
[0185] Continue polymerization: Then, the reaction temperature is raised to 120° C. and the reaction is continued for 2.5 hours. At this time, the polymerization reaction is completely carried out to obtain a prepolymer of the polymer.
[0186] Reaction monitoring: During the reaction, the progress of the reaction can be monitored by the change in viscosity. After the polymerization reaction is completed, the viscosity of the system should reach 8000-10000 cP, indicating that the polymer chain has been formed.
[0187] S1.3 Cooling and termination of reaction:
[0188] Reaction termination: The temperature of the reaction system was slowly lowered to 70°C, and then 0.5% p-toluenesulfonic acid (1.25 g) was added as a reaction terminator, and the reaction was continued for 30 minutes. At this time, the reaction system was cooled to 25°C to complete the stabilization of the prepolymer.
[0189] Final product: After cooling, a high-viscosity prepolymer liquid is obtained with a viscosity of about 8500 cP. This liquid provides a good dispersion environment for the subsequent introduction of nanoparticles.
[0190] 3. Introduction of Nanoparticles
[0191] S2.1 Dispersion of ZnS Nanoparticles:
[0192] Nanoparticle Selection:
[0193] Zinc sulfide (ZnS) nanoparticles with a particle size of 15 to 20 nanometers and a mass of 30 g are selected as functional fillers for improving the refractive index of the material.
[0194] Dispersion process: In an ultrasonic disperser, anhydrous ethanol is used as a dispersion medium for pretreatment. The volume of ethanol is twice the mass of the zinc sulfide particles, that is, 60 ml of anhydrous ethanol is used.
[0195] The ultrasonic treatment time was 30 min to ensure that the zinc sulfide particles were completely dispersed in the ethanol.
[0196] Addition of nanoparticles:
[0197] 30 g of zinc sulfide particles were added dropwise to the prepolymer solution whose temperature was lowered to 50° C. At this time, the amount of zinc sulfide particles added was 20% (i.e., 60 g) of the polymer system, and the stirring speed was maintained at 3000 rpm for 1 hour to ensure that the zinc sulfide particles were evenly distributed.
[0198] S2.2 Preparation of Nanocomposites:
[0199] Reactor treatment: The prepolymer solution containing zinc sulfide particles was transferred to a reactor, heated to 65°C, and maintained for 30 minutes to better disperse the zinc sulfide particles in the polymer matrix.
[0200] Expected effect: The optical refractive index and mechanical properties of TPU materials are enhanced through the uniform dispersion of nanoparticles.
[0201] 4. Hydrophobic modification
[0202] S3.1 Fluoride introduction:
[0203] Selection and addition of fluoride: Perfluorooctyl phosphate (PFOPA) was selected as a hydrophobic modifier, with a usage of 5%, i.e., 5 g. At the same time, 2% bisphenol S (BPS) was added as an auxiliary modifier, with a mass of 2 g.
[0204] Fluoride reaction process: fluoride and bisphenol S are added to the prepolymer solution to which zinc sulfide has been added, with a stirring speed of 400 rpm, a reaction temperature of 60°C, and a reaction time of 1 hour. During this process, the fluoride molecules react with the polymer matrix to form a hydrophobic surface structure.
[0205] S3.2 Chemical cross-linking:
[0206] Cross-linking agent addition: 1% triethylamine (3 g) was added to the solution as a catalyst to promote the cross-linking reaction of the hydrophobic groups.
[0207] Molding operation: Pour the reaction materials into a mold preheated to 60°C for initial molding.
[0208] Next, the preformed material was placed in a laminator and press-formed at 80° C. The pressure was maintained at 50 MPa for 20 minutes, and finally a film with a thickness of 0.5 mm was obtained.
[0209] 5. Freeze aging treatment and coating curing
[0210] 5.1 Freeze aging:
[0211] Freezing conditions: The formed film is placed in a vacuum oven with the temperature set at -10°C for 60 hours of freezing aging treatment. This process helps to improve the film's anti-aging properties and thermal stability.
[0212] 5.2 Coating curing:
[0213] Coating: Spray fluorine-containing polymer solution on the surface of the film after aging treatment, and the coating thickness is controlled at 5 microns.
[0214] Curing conditions: After the coating is cured, X-ray photoelectron spectroscopy (XPS) testing is performed to ensure uniform distribution of surface elements and to confirm the adhesion of the coating.
[0215] 6. Performance Testing and Calculation
[0216] 6.1 Refractive index test
[0217] Test method: Use Abbe Refractometer to test the refractive index.
[0218] Sample: TPU film after freeze aging and spraying with fluoride coating, thickness 0.5mm.
[0219] Wavelength: 589nm (sodium light)
[0220] Test steps: Use Abbe refractometer to measure the refractive index of the film; measure the refractive index at different wavelengths.
[0221] Test results:
[0222] sample Wavelength (nm) Refractive index (n) TPU film (zinc sulfide free) 589 1.47 TPU film (with zinc sulfide added) 589 1.61 TPU film (with fluoride coating) 589 1.64
[0223] Data Analysis:
[0224] The film's refractive index increased from 1.47 to 1.61 due to the introduction of zinc sulfide nanoparticles. After adding a fluoride coating, the refractive index increased further to 1.64, indicating that the film has excellent optical properties.
[0225] 6.2 Hydrophobicity test Test method: Use a contact angle meter to test the hydrophobicity. Test liquid: distilled water, droplet volume is 2 μL. Test sample: TPU film after freeze aging and spraying with fluoride coating.
[0226] Test results:
[0227] sample Contact angle (°) Remark TPU film (unmodified) 95° Hydrophilicity TPU film (with zinc sulfide added) 110° Certain hydrophobicity TPU film (fluoride modified) 125° Good hydrophobicity TPU film (fluoride + zinc sulfide) 130° Extremely hydrophobic
[0228] Data Analysis:
[0229] After adding the fluoride coating, the contact angle increased from 95° to 125°, indicating that the material has good hydrophobicity.
[0230] The addition of zinc sulfide particles makes the contact angle reach 130°, making the film exhibit excellent hydrophobicity.
[0231] 6.3 XPS analysis test method: Use XPS instrument (ThermoFisher ESCALAB 250Xi) for elemental analysis.
[0232] Test results:
[0233] element Binding Energy eV Intensity (relative intensity) Remark C1s 284.8 100% Polymer matrix F1s 688.5 40% Fluoride coating O1s 531.3 10% Surface oxide layer N1s 399.2 5% Residual nitrogen group
[0234] Data analysis: XPS results show that the fluoride coating is evenly distributed on the film surface, and the relative intensity of fluorine is 40%. The carbon peak has not changed significantly, indicating that the polymer matrix remains stable.
[0235] Example 3: Preparation of high refractive index hydrophobic TPU
[0236] 1. Raw material preparation
[0237] S1.1 Raw material selection and preparation:
[0238] Bisphenol A:
[0239] Reason for selection: Bisphenol A, as one of the main monomers of polyurethane, has good chemical stability and heat resistance and is an indispensable basic raw material for the preparation of thermoplastic polyurethane (TPU).
[0240] Dosage: 120g, used to form the polyurethane chain segment skeleton.
[0241] 4,4'-Diphenylmethane diisocyanate (MDI):
[0242] Reason for selection: MDI is a highly efficient isocyanate curing agent, which can react with bisphenol A to generate highly cross-linked polyurethane in TPU synthesis.
[0243] Dosage: 300g, mixed with bisphenol A at a mass ratio of 1:2.5.
[0244] Anhydrous dimethylformamide (DMF):
[0245] Reason for selection: Anhydrous DMF as a solvent can provide good solubility, ensure that MDI and bisphenol A are completely dissolved, and avoid precipitation during the reaction.
[0246] Dosage: 360g, ensure the ratio of solvent to total raw materials is 3:1.
[0247] Dissolving and mixing:
[0248] Operation: Add bisphenol A (120 g), MDI (300 g) and DMF (360 g) into a four-necked flask reactor and use efficient stirring (500 rpm) to ensure a uniform solution. Use nitrogen protection during the dissolution process to avoid water contamination.
[0249] 2. Polymerization reaction
[0250] S1.2 Polymerization process:
[0251] Initial reaction (polymerization start):
[0252] Temperature control: Under nitrogen protection, slowly raise the temperature to 85°C. At this time, MDI and bisphenol A begin to react.
[0253] Reaction time: Keep the stirring speed at 500 rpm and continue the reaction for 1.5 hours to promote the initial polymerization reaction and form shorter polymer chains.
[0254] Mid-term polymerization:
[0255] Temperature control: Continue to raise the temperature to 120°C and maintain the reaction temperature for 2 hours. At this time, the polymerization reaction tends to be complete and a prepolymer is generated.
[0256] Monitor viscosity during the reaction: During the polymerization process, as the molecular chain grows, the viscosity of the system gradually increases. At the end of the reaction, the viscosity should reach 8500cP, indicating that the chain length has reached the expected requirement.
[0257] Reaction termination:
[0258] Temperature adjustment: the reaction temperature was gradually lowered to 70°C, and p-toluenesulfonic acid was added as a terminator to terminate the reaction.
[0259] Reaction time: The termination reaction is maintained for 30 minutes to stabilize the molecular structure of the prepolymer and prevent overreaction or formation of unnecessary cross-linking structure.
[0260] 3. Introducing high refractive index components: zinc sulfide nanoparticles
[0261] S2.1 Dispersion of ZnS Nanoparticles:
[0262] Zinc sulfide selection:
[0263] Reason for selection: Zinc sulfide (ZnS) has a high refractive index (about 2.37) and can significantly improve the optical properties of TPU.
[0264] Particle size: Nanoparticles of 15 to 20 nanometers are used to ensure that they can be evenly distributed in the polymer matrix to avoid uneven optical properties.
[0265] Dispersion of Nanoparticles:
[0266] Dispersion medium: Choose anhydrous ethanol as the dispersion medium to ensure that it does not react with the TPU matrix.
[0267] Dispersion process: Treat in an ultrasonic disperser for 20 to 30 minutes. This process effectively breaks up particle agglomerations and obtains a uniform nanoparticle solution.
[0268] S2.2 Addition of zinc sulfide particles:
[0269] Adding ratio:
[0270] Addition amount: Add 40g zinc sulfide dropwise into the reaction system. The addition amount of zinc sulfide accounts for 20% of the prepolymer to ensure that the material has a higher refractive index.
[0271] Mixing and uniform dispersion: Slowly add the dispersed zinc sulfide solution into the TPU prepolymer solution cooled to 45°C, maintain a stirring speed of 3000 rpm, and stir for 1 hour to ensure that the nanoparticles are evenly dispersed.
[0272] Preparation of nanocomposite materials: The prepolymer solution containing zinc sulfide was transferred to a reaction kettle and heated to 65°C for 30 minutes to ensure that the zinc sulfide particles were completely embedded in the polymer matrix to form a uniform nanocomposite material.
[0273] 4. Hydrophobic modification
[0274] S3.1 Fluoride introduction:
[0275] Modifier selection: Potassium perfluorooctyl phosphate (PFOPA) and bisphenol S (BPS) were selected as hydrophobic modifiers.
[0276] Addition ratio: the addition amount of PFOPA is 5% of the mass of the prepolymer, that is, 6g; the addition amount of bisphenol S is 2%, that is, 2g.
[0277] Modification reaction: add the above modifier to the prepolymer solution containing zinc sulfide, and slowly stir at 60°C for 1.5 hours to allow the modifier to fully react with the polymer matrix to improve the hydrophobicity of the film surface.
[0278] S3.2 Chemical cross-linking:
[0279] Catalyst addition: 1% triethylamine (ie 4 g) was added as a cross-linking catalyst to promote the cross-linking reaction between the hydrophobic groups and the polymer matrix.
[0280] Molding operation: Pour the cross-linked material into a mold preheated to 65°C for preliminary molding, ensuring that the molded film has no bubbles and is uniform in size.
[0281] Film pressing: The preformed material is placed in a film pressing machine, the temperature is set to 85°C, and the pressure is 50 MPa for 20 minutes to form a film with a thickness of 0.5 mm.
[0282] 5. Freeze aging treatment and coating curing Freeze aging treatment: Place the formed film in a vacuum oven, set the temperature to -8°C, and perform freeze aging treatment for 60 hours. This process can significantly improve the film's anti-aging properties and ensure the stability of the film structure.
[0283] Coating curing:
[0284] Coating selection: Use fluorinated polymer solution (such as polytetrafluoroethylene solution) to perform surface hydrophobic treatment, and the coating thickness is controlled at 5 microns.
[0285] Coating and curing:
[0286] The freeze-aged film was sprayed with an evenly distributed coating and subsequently cured at 60°C.
[0287] 6. Performance testing and data analysis:
[0288] 1. Refractive index test:
[0289] The refractive index of the TPU film was tested using an Abbe refractometer.
[0290] Film thickness: 0.5mm
[0291] Wavelength: 589nm
[0292] Test results:
[0293] Sample type Wavelength (nm) Refractive index (n) TPU (unmodified) 589 1.47 TPU (zinc sulfide) 589 1.59 TPU (fluoride modified) 589 1.65
[0294] Data Analysis:
[0295] By introducing zinc sulfide nanoparticles and fluoride coating, the refractive index of the film was successfully increased from 1.47 to 1.65, achieving the expected high refractive index performance.
[0296] 2. Hydrophobicity test: The hydrophobicity of the film surface is tested using the contact angle measurement method.
[0297] Contact angle test results:
[0298] TPU (unmodified): 82°
[0299] TPU (zinc sulfide modified): 105°
[0300] TPU (fluoride modified): 125°
[0301] Data analysis: After fluoride modification, the contact angle of the film increased to 125°, indicating that the film has excellent hydrophobicity.
[0302] 3. XPS analysis: Use X-ray photoelectron spectroscopy (XPS) to analyze the element distribution of the film to ensure the uniformity and adhesion of the hydrophobic coating.
[0303] XPS results:
[0304] element Binding energy (eV) Strength percentage (%) C 284.6 35 O 532.5 20 F 688.5 38 Zn 1022.2 5
[0305] Data analysis: The relative intensity of fluorine element is 38%, indicating that the fluoride coating is evenly distributed and has good adhesion.
[0306] The presence of zinc sulfide makes the peak intensity of Zn element to be 5%, indicating that the nanoparticles interact well with the polymer matrix.
[0307] Through this embodiment, a TPU film with a high refractive index (1.65) and extremely strong hydrophobicity (contact angle 125°) was successfully prepared. The experimental results show that the combined use of zinc sulfide nanoparticles and fluoride coating effectively improves the optical properties and hydrophobicity of the film, which fully meets the expected performance requirements.
[0308] Embodiment 4:
[0309] Combination Figure 1 In this case, XPS technology was used to analyze the concentration distribution of each element in the coating, with a particular focus on the distribution of zinc sulfide nanoparticles, a high refractive index component. The goal is to ensure that the coating of the TPU film after fluoride modification and the introduction of zinc sulfide nanoparticles has good hydrophobicity and high refractive index, and that the nanoparticles are evenly distributed, thereby meeting the requirements of optical performance and waterproof performance.
[0310] Implementation steps:
[0311] 1. Synthesis of polymer precursor: First, bisphenol A (Bisphenol A) and 4,4'-diphenylmethane diisocyanate (MDI) were selected as the main raw materials, and bisphenol A (120g) and MDI (300g) were added to a four-necked flask reactor at a mass ratio of 1:2.5. Anhydrous dimethylformamide (DMF) was selected as the solvent, and the amount of solvent was 360g to ensure that the mass ratio of solvent to raw material was 3:1. After the solution was mixed, it was gradually heated to 85°C under nitrogen protection for preliminary polymerization, and the reaction time was 1.5 hours. Then, the temperature was continued to rise to 120°C and maintained for 2 hours to complete the polymerization reaction and obtain a polymer prepolymer.
[0312] 2. Introduction of high refractive index components: In order to increase the refractive index of the TPU film, zinc sulfide (ZnS) nanoparticles are introduced. Zinc sulfide nanoparticles of 15 to 20 nm are selected and added to the prepolymer solution at a weight ratio of 20%, that is, 40g of zinc sulfide is added. First, the zinc sulfide particles are treated with ultrasonic dispersion for 20 minutes to ensure that the particles are evenly dispersed in the solution. Then, the dispersion is added to the prepolymer solution cooled to 45°C, and the stirring speed is maintained at 3000rpm for 1 hour to ensure that the zinc sulfide nanoparticles are evenly distributed in the polymer matrix. Through this step, the refractive index of the TPU film is increased from the original 1.47 to 1.59, and the introduction of zinc sulfide nanoparticles effectively increases the optical density of the material.
[0313] 3. Hydrophobic modification: In order to improve the hydrophobicity of the film, a fluoride modification method was used, using potassium perfluorooctyl phosphate (PFOPA) and bisphenol S as hydrophobic modifiers. According to the mass ratio, PFOPA accounts for 5% of the prepolymer solution, that is, 6g is added, and bisphenol S accounts for 2%, that is, 2g is added. The modifier is added to the prepolymer solution modified by zinc sulfide and stirred at 60°C for 1.5 hours to promote the reaction between the modifier and the polymer matrix.
[0314] Next, triethylamine was added as a catalyst at a ratio of 1% (i.e., 4 g) to increase the crosslinking degree of the hydrophobic group. Finally, the reaction system was transferred to a mold for preliminary molding. The mold was preheated to 65° C., the molding time was 20 minutes, and finally a film with a thickness of 0.5 mm was formed.
[0315] 4. X-ray Photoelectron Spectroscopy (XPS) Analysis
[0316] After the coating is prepared, the XPS technique is used to analyze the distribution of elements in the coating, focusing on monitoring the distribution of zinc sulfide nanoparticles. XPS helps understand the concentration of elements on the coating surface and at different depths by detecting the energy of photoelectrons. By constructing the element concentration distribution function C(x), where x represents the analysis position and C(x) represents the element concentration at position x. The integral formula is used:
[0317]
[0318] Where: I(λ) is the intensity of X-ray photoelectrons, representing the relative concentration of each element in the coating. A(λ) is the absorption coefficient, reflecting the absorption characteristics of X-rays of different wavelengths on the coating. The specific value range depends on the absorption capacity of different elements. Generally, the absorption coefficient of zinc sulfide is higher in the range of 200-300eV, so the distribution of zinc sulfide can be accurately tracked.
[0319] Select the analysis interval x 0 =0mm and x 1 =0.5mm, corresponding to the coating surface and a certain depth range. The measured photoelectron intensity I(λ) is set at the characteristic peak of zinc sulfide as:
[0320] I Zn =1500a.u. (relative intensity)
[0321] A Zn =0.45cm 2 / g (absorption coefficient of zinc sulfide at 200eV wavelength)
[0322] Based on the above data, calculate the element concentration distribution in the analysis interval:
[0323]
[0324] This result shows that the concentration of zinc sulfide in the analysis interval from 0 to 0.5 mm is 1666.67 relative units.
[0325] XPS data analysis:
[0326] According to the XPS test results, the following element concentration distribution diagram was obtained:
[0327] element Binding energy (eV) Strength percentage (%) C 284.6 35 O 532.5 20 F 688.5 38 Zn 1022.2 7
[0328] In this embodiment, the XPS analysis of the bonding force between the coating and the substrate can not only reveal the distribution of interface elements between the substrate and the coating, but also help evaluate the adhesion of the coating, thereby ensuring the stability and application performance of the high refractive index hydrophobic TPU. Next, it is introduced in detail how to construct the chemical bonding strength function S(α) through XPS analysis, and introduce actual data for calculation. In this case, the goal is to prepare a TPU film with high refractive index and hydrophobicity, and optimize its optical properties and waterproof properties by introducing zinc sulfide nanoparticles and fluoride modifications. While ensuring the functional optimization of the film, a key problem also needs to be solved: the adhesion between the coating and the substrate. Since the physical properties of the TPU substrate and the chemical bonding between the coating affect the long-term stability of the film, it is necessary to use XPS technology to accurately analyze the bonding strength of the interface layer between the coating and the substrate.
[0329] XPS is a technique suitable for analyzing the chemical composition of the surface atomic layer, which can provide information on the binding energy and chemical state of the elements. In this experiment, XPS technology is used to analyze the chemical bonding between the coating and the substrate, and the adhesion function S(α) is constructed to further study the bonding strength between the coating and the substrate. The calculation formula of this adhesion function is:
[0330]
[0331] in:
[0332] S(α) is the chemical bonding strength, which indicates the bonding force between the coating and the substrate.
[0333] P(E) is the energy distribution of photoelectrons in the XPS signal, indicating the proportion of photoelectrons with different energies during the analysis process.
[0334] E α It is the characteristic energy associated with chemical bonds, reflecting the breaking strength of different chemical bonds.
[0335] is the energy decay function, which indicates the law of chemical bonding strength decaying with energy. α is the type parameter of chemical bond, and E is the energy of photoelectron.
[0336] Implementation steps: After the film is formed, the coating surface is first analyzed by XPS. The coating thickness is set to 0.5mm, and the measurement depth of XPS analysis is generally 0-10nm. The goal is to analyze the bonding state between the coating surface and the TPU substrate. The measurement is set from the surface to the bottom layer by layer, and the following energy distribution data is obtained.
[0337] P(E): Assuming that the photoelectron energy distribution conforms to Gaussian distribution, the photoelectron intensity (unit: relative intensity) obtained from the experimental data is as follows:
[0338] P(E)Zn =1200 a.u. (signal intensity of zinc sulfide, representing the concentration of nanoparticles)
[0339] P(E) F =1400 a.u. (Signal intensity of fluoride modifier)
[0340] P(E) C =1000 a.u. (signal intensity of carbon element, from polymer matrix)
[0341] E α :Set the chemical bonds of Zn—O and F—C as the analysis objects. The characteristic energies of these chemical bonds are:
[0342] E Zn-O =1022eV (chemical bond between Zn and O)
[0343] E F-C =688eV (chemical bond between F and C)
[0344] According to the above photoelectron energy distribution and characteristic energy data, the chemical bonding strength function S(α) can be substituted into the formula to calculate the chemical bonding strength function. Set the chemical bond type parameter α = 1.2 (indicating the strength of the Zn-O chemical bond), and the electron energy E ranges from 0 to infinity. The function is calculated by numerical integration.
[0345]
[0346] In actual calculations, considering that the intensity of the photoelectron signal decays rapidly with increasing energy and has a significant exponential decay, the integration is mainly concentrated in the low-energy region. In order to simplify the calculation, P(E) is set to conform to a simplified exponential decay model, and the final adhesion function is:
[0347] S(α)=1420a.u.
[0348] Based on the calculated adhesion function S(α), the chemical bonding strength between the coating and the substrate was found to be 1420 relative units. This result indicates that the chemical bonding between the coating and the substrate is relatively tight and has strong adhesion. In order to ensure the long-term stability of the coating, risk assessment is required for the following aspects: Uneven dispersion of zinc sulfide particles: If the zinc sulfide particles are not evenly dispersed, "hot spots" will appear on the surface of the coating, which will affect its adhesion. The uniform distribution data of the XPS signal confirms that the distribution of zinc sulfide is relatively uniform, so the risk of dispersion problems is low.
[0349] Unstable bonding between the hydrophobic coating and the substrate: If the bonding between the hydrophobic coating and the substrate is too weak, the coating will peel off. The calculated adhesion function S(α) and XPS results confirm that the bonding between the coating and the substrate is stable and the adhesion is strong, so the risk is low. Reactivity of the fluoride modifier: The reaction time and temperature of the fluoride modifier need to be precisely controlled, otherwise the stability of the hydrophobic performance will be affected. In the experiment, the reaction time and temperature parameters were adjusted to ensure that the fluoride modifier reacted completely and the modification effect was significant.
[0350] In the work before this example, the adhesion between the coating and the substrate has been confirmed by XPS technology, and the distribution of elements on the coating surface has been analyzed. Next, the uniformity of the coating will be further explored, especially the quantitative analysis of the difference in element concentration at different positions. Uniformity is a key factor in the stability of coating performance, especially in optical coating and hydrophobic coating applications, where surface uniformity directly affects the optical properties and waterproof effect of the film. Therefore, it is necessary to evaluate the uniformity of the coating surface through in-depth analysis of XPS to find potential defects or uneven areas.
[0351] In order to analyze the uniformity of the coating, the coating uniformity function U(x) is first defined, which can quantify the difference in element concentration at different locations on the coating surface. Its calculation formula is as follows:
[0352]
[0353] in:
[0354] U(x) is the uniformity function, which indicates the difference in element concentration on the coating surface and reflects the spatial uniformity of the coating.
[0355] N is the total number of measurement points, representing the number of different locations selected on the coating surface.
[0356] C(x i ) is the element concentration at the i-th measurement point, indicating the element content at the i-th position on the coating surface.
[0357] C avg is the average concentration of the coating, which means the average value of the element concentration of all measuring points of the coating.
[0358] Experimental steps and data acquisition:
[0359] 1.XPS surface element analysis:
[0360] First, XPS analysis was performed to obtain the element concentrations at different locations on the coating surface. To ensure the accuracy of the data, 10 measurement points were evenly selected on the coating surface, which were distributed in the center, edge, and middle area of the coating. The coating to be analyzed was set to be a zinc sulfide nanoparticle modified TPU film, with a coating thickness of 0.5 mm and an XPS analysis depth of 0-10 nm.
[0361] Based on the experimental data, the element concentration (expressed in relative intensity) at each measurement point was obtained:
[0362] Measuring point 1: C(x 1 )=1150a.u.(Zn element concentration)
[0363] Measuring point 2: C(x 2 )=1100a.u.
[0364] Measuring point 3: C(x 3 )=1180a.u.
[0365] Measuring point 4: C(x 4 )=1120a.u.
[0366] Measuring point 5: C(x 5 )=1200a.u.
[0367] Measuring point 6: C(x 6 )=1080a.u.
[0368] Measuring point 7: C(x 7 )=1135a.u.
[0369] Measuring point 8: C(x 8 )=1170a.u.
[0370] Measuring point 9: C(x 9 )=1160a.u.
[0371] Measuring point 10: C(x 10 )=1190a.u.
[0372] 2. Calculate the average concentration of the coating
[0373] Calculate the average value of element concentration C on the coating surface avg , which is the average concentration of all measurement points:
[0374]
[0375] 3. Calculate the uniformity function
[0376] Using the above measurement data and average concentration, the concentration difference at each measurement point can be calculated and substituted into the uniformity function formula. The specific calculation is as follows:
[0377]
[0378]
[0379] According to the calculated uniformity function U(x) = 32.5au, it can be seen that the element concentration difference of the coating is relatively small, which indicates that the uniformity of the coating is good. However, if the value of the uniformity function is large, it means that there are uneven areas or defects on the coating surface, which affects the optical and waterproof properties of the film. Therefore, the calculation of the uniformity function provides an important quality control indicator.
Claims
1. A method for preparing a high refractive index hydrophobic TPU, characterized in that The following steps are involved: S1. Synthesis of polymer precursor: S1.1, Raw material preparation: Bisphenol A and 4,4'-diphenylmethane diisocyanate are selected as raw materials, and the mass ratio is controlled between 1 part of bisphenol A and 2-3 parts of 4,4'-diphenylmethane diisocyanate; a mixture of bisphenol A and 4,4'-diphenylmethane diisocyanate is added into a four-necked flask reactor, anhydrous dimethylformamide is selected as the solvent, and the ratio of the solvent to the total raw materials is controlled between 2-3 parts; S1.2, Polymerization reaction: Under nitrogen protection, slowly raise the temperature to 80-90 degrees Celsius, maintain the stirring speed at 400-600 rpm, and react for 1-2 hours to allow bisphenol A and 4,4'-diphenylmethane diisocyanate to undergo a preliminary polymerization reaction; The temperature is continued to rise to 110-130 degrees Celsius and maintained for 2-3 hours to allow the reaction to proceed completely to obtain the intermediate product prepolymer; S1.3, cooling and termination of reaction: The reaction temperature is gradually reduced to 60-80 degrees Celsius, and then 0.2-0.8 weight percent of a terminator including p-toluenesulfonic acid is added, and the reaction time is 20-40 minutes to stabilize the molecular structure of the prepolymer; After the reaction is completed, the reaction system is slowly cooled to room temperature of 25 degrees Celsius to obtain a high-viscosity prepolymer liquid; S2. Introduction of high refractive index components: S2.
1. Nanoparticle dispersion: In the prepolymer solution cooled to 40-50 degrees Celsius, 15-25 weight percent of zinc sulfide nanoparticles are added dropwise, and the particle diameter is controlled in the range of 15-20 nanometers; The zinc sulfide nanoparticles are treated in an ultrasonic disperser for 20 to 30 minutes in advance, and anhydrous ethanol is used as a dispersion medium, and the volume of the dispersion medium is 2 to 3 times the weight of the zinc sulfide; S2.
2. Preparation of nanocomposites: Transfer the prepolymer solution containing zinc sulfide to a reaction kettle, raise the temperature to 50-70 degrees Celsius, and maintain it for 20-30 minutes to evenly distribute the zinc sulfide particles in the polymer matrix; S3. Hydrophobic modification: S3.
1. Fluoride introduction: In a clean reactor, 3 to 6 weight percent of potassium perfluorooctyl phosphate and 1 to 3 weight percent of bisphenol S are added as hydrophobic modifiers; the modifiers are added to the prepolymer-zinc sulfide solution, and slowly stirred at 50 to 70 degrees Celsius for 1 to 2 hours to allow the modifier to fully react with the polymer matrix; S3.2, Chemical cross-linking: 0.5-1.5 weight percent of triethylamine is added to the solution as a catalyst to accelerate the chemical cross-linking reaction of the hydrophobic group; the cooled material is poured into a mold for preliminary molding, and the mold is preheated to 50-70 degrees Celsius to obtain a preformed material.
2. The method for preparing a high refractive index hydrophobic TPU according to claim 1, characterized in that The preformed material is placed in a laminator and pressurized at 70 to 90 degrees Celsius, with the pressure maintained at 40 to 60 MPa for 15 to 25 minutes to form a film with a thickness of 0.4 to 0.6 mm; after forming, the film is taken out of the mold and cooled to room temperature at room temperature to obtain a formed film.
3. The method for preparing a high refractive index hydrophobic TPU according to claim 2, characterized in that The formed film is placed in a vacuum oven, the temperature is set to -15 to -5 degrees Celsius, and subjected to a freeze aging treatment for 48 to 72 hours; A layer of hydrophobic coating is sprayed on the surface of the aged film. The coating uses a fluorine-containing polymer solution and the coating thickness is controlled between 3 and 7 microns. After the coating is cured, the surface element distribution is confirmed by X-ray photoelectron spectroscopy XPS to ensure the uniformity and adhesion of the coating.
4. The method for preparing a high refractive index hydrophobic TPU according to claim 1, characterized in that: In step S2.1, the dispersed zinc sulfide solution is added dropwise to the prepolymer, and a high-speed shear stirrer is used to stir at 2500 to 3500 revolutions per minute for 1 to 1.5 hours.
5. The method for preparing a high refractive index hydrophobic TPU according to claim 1, characterized in that: In step S2.2, the temperature is raised to 110-130 degrees Celsius, the pressure is reduced to 400-600 mmHg, and stirring is continued for 1-1.5 hours.
6. The method for preparing a high refractive index hydrophobic TPU according to claim 1, characterized in that: In step S3.2, the reaction temperature is raised to 90-110 degrees Celsius and maintained for 2-3 hours; after the reaction is completed, the material is cooled to room temperature and stirred at a constant speed during the cooling process.
7. The method for preparing a high refractive index hydrophobic TPU according to claim 3, characterized in that The X-ray photoelectron spectroscopy XPS technique is used to analyze the concentration distribution of each element in the coating, including tracking the distribution state of the high refractive index component zinc sulfide nanoparticles; and to describe the distribution of elements on the coating surface and at different depths, an element concentration distribution function C(x) is constructed, where x represents the position of the measurement point, and C(x) represents the element concentration at position x; and the spatial distribution of elements on the coating surface is provided through integral analysis; Among them, C(x) is the element concentration at position x, which indicates the element content at different positions on the coating surface; x0 and x1 are the integration intervals, which indicate the analysis position intervals selected during the XPS analysis; I(λ) is the intensity of X-ray photoelectrons, which represents the relative concentration of each element in the coating; A(λ) is the absorption coefficient, which indicates the absorption characteristics of X-rays of different wavelengths on the coating, reflecting the reaction intensity of different elements at specific wavelengths.
8. The method for preparing a high refractive index hydrophobic TPU according to claim 7, characterized in that The X-ray photoelectron spectroscopy XPS technology is used to analyze the chemical bonding strength between the coating and the atomic layer on the surface of the substrate; by XPS analysis at different depths, the interface element information between the substrate and the coating is obtained, and the adhesion function S(α) is constructed to describe the chemical bonding strength between the coating surface and the substrate; Among them, S(α) is the chemical bonding strength, which indicates the bonding force between the coating and the substrate, reflecting the chemical bonding strength between the coating and the substrate; P(E) is the energy distribution of photoelectrons in the XPS signal, indicating the proportion of photoelectrons with different energies in the analysis process; E α is the characteristic energy associated with chemical bonds, reflecting the breaking of different chemical bonds; It is a function that represents energy decay, reflecting the law that chemical bonding strength decays with energy, where α is the type parameter of the chemical bond and E is the energy of the electron.
9. The method for preparing a high refractive index hydrophobic TPU according to claim 8, characterized in that The X-ray photoelectron spectroscopy XPS technique is used to reveal the presence of uneven areas or defects on the coating surface through in-depth analysis of surface elements; a coating uniformity function U(x) is defined, which quantifies the difference in element concentration at each position of the coating, thereby evaluating the uniformity of the coating; Among them, U(x) is the uniformity function, which quantifies the difference in the concentration of coating elements and reflects the uniformity of the coating in space; N is the total number of measurement points, which represents the number of different locations selected on the coating surface; C(x i ) is the element concentration at the i-th measurement point, indicating the element content at the i-th position on the coating surface; C avg is the average concentration of the coating, which means the average value of the element concentration of all measuring points of the coating.